Eumycetoma Pedis Due to Madurella mycetomatis in Indonesian Farmer: A Case Report - Hutabarat, Emma Novauli; Ilyas, Faridha; Amin, Safruddin (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Mycetoma is a chronic, localized cutaneous inflammatory disease originating from fungi (eumycetoma) or bacteria (actinomycetoma) infection. The most common cause of eumycetoma is a black grain producing fungus, Madurella mycetoma. CASE PRESENTATION: We present a case of eumycetoma pedis in a middle-aged woman with a successful resolution after receiving the combination of surgical debridement, systemic itraconazole, and topical antifungals therapy. CONCLUSION: This case report highlights the importance of a prompt diagnostic procedure to identify the causative agent in mycetoma at an early stage of the disease followed by integrated management care that combines systemic therapy and surgical intervention.